Retro-techno-economic evaluation of acetic acid production using cotton stalk as feedstock - SAYAR, AHMET ALP; SARIYAR AKBULUT, BERNA; KAZAN, DİLEK; SAYAR, NİHAT ALPAGU; PİNAR, ORKUN (SPRINGER, 2018)
In value-added chemical industries, use of agricultural wastes as raw materials remains to be a major challenge in commercialization due to lack of competitiveness with respect to petrochemical processes. This work presents the techno-economic analysis of a novel bioprocessing plant converting 356,400MT/year cotton stalks into 147,000MT/year acetic acid. A production scheme integrating lignin separation with the main bioconversion stages has been proposed. Techno-economic assessment was performed through economic feasibility and retro-techno-economic analysis (RTEA) methods. The RTEA method has been extended to include the estimation of research and development funding for improving economic feasibility. Carbon offset of the proposed technology has been estimated and carbon credit results have been incorporated into the economic feasibility metrics.
Keywords: Acetic acid; Cotton stalk; Retro-techno-economic analysis; Carbon offset; Bioprocess design; FERMENTATION